Correction: Wild-type and mutated IDH1/2 enzymes and therapy responses. Issue 43 (25th October 2018) - Molenaar, Remco; Maciejewski, Jaroslaw; Wilmink, Johanna; Noorden, Cornelis
The originally published version of this article contained an error in Figure 2. On the IDH1/2 mutated arrow, it incorrectly read 'NADP+ ->NADPH' instead of the correct 'NADPH ->NADP+ '. This has now been corrected in the PDF and HTML versions of the article. The authors wish to apologize for any inconvenience caused.